Smart photoluminescent nanohybrids based on CdSe quantum dots capped with multidentate thiolated pH‐responsive and thermoresponsive polymers for nanosensing. Issue 21 (22nd August 2014) - Liras, Marta; Peinado, Elena; Cañamero, Pedro; Quijada‐Garrido, Isabel; García, Olga
ABSTRACT Well‐defined thermoresponsive polymers obtained by the atom transfer radical polymerization (ATRP) of short oligo(ethylene glycol) methyl ether methacrylates (MEOnMA, n = 2, 3, or 8) with small ratios of a thiolated comonomer, 2‐(acetylthio)ethylmethacrytale, can replace the hydrophobic trioctylphosphine oxide (TOPO) capping of CdSe quantum dots (QDs). After this facile ligand exchange, the mild hydrolysis of the acetylthiol group into thiol is the key to enhance the QD luminescence. However, the length of the ethylene glycol side chain is critical for the success of the functionalization; it is established that the shortest MEO2MA‐based copolymers result in a compact coating and a highest quantum yield (up to a factor of 6) when compared with that of CdSe@TOPO in dichloromethane. In addition, the amphiphilic character of the copolymer allows the CdSe@P(MEOnMA‐co‐SEMA) nanohybrids to disperse in water. On the other hand, the residual ionizable thiol groups do not get attached to the QD surface, cause that the lower critical solubility temperature of the polymer depends on pH as well. Thus, at acidic pH, an abrupt increase in the luminescence emission accompanies the polymer collapse, which establishes the promise of these hybrids as temperature/pH nanosensors and targeted drug delivery. © 2014 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2014, 52, 3087–3095